MEMBANGUN GERAKAN MUTU DI LEMBAGA PENDIDIKAN ISLAM - Lestari, Tri; Mutohar, Prim Masrohan; Muhajir, As’aril (SKILLS : Jurnal Riset dan Studi Manajemen Pendidikan Islam, 2023)
The quality of education will not succeed without an appropriate strategy for improving the quality of all components. The problems that occur include teacher professionalism, graduate competency standards, effective learning, and programs that do not support quality achievement. One of the efforts to improve quality is through the implementation of strategic management so as to be able to determine the right strategy to improve the quality of education. Improving the quality of education is a top priority in all educational institutions. Likewise in Islamic educational institutions which are currently in the process of becoming educational institutions that have the same quality as other educational institutions and even become educational institutions of high quality. To achieve this, efforts continue to be made by Islamic educational institutions. One of the efforts is to apply various theories and concepts of quality management so that the quality of education can be maintained and recognized as an educational institution that carries out processes well and produces good output. There are several concepts of quality/quality improvement put forward by experts such as those relating to quality planning, quality control and improvement. This study will discuss several concepts of quality and their relevance to Islamic educational institutions. While the quality of education will not succeed without the right strategy for improving the quality of all components, the problems that occur include teacher professionalism, graduate competency standards, effective learning, and programs that do not support quality achievement. One of the efforts to improve quality is through the implementation of strategic management to be able to determine the right strategy to improve the quality of education.